Education Human Capital Development and Per Capita Income in Nigeria: A Bivariate Granger Causality Analysis - Agu, Sunday Virtus; Azike, Lawrence Chike; Kalu, U. Chris (Social Science Research, 2023)
Despite government efforts to promote adequate education and to reduce the negative consequence of inadequate educational system for human capital development, educational outcomes in Nigeria lags behind when compared with other countries even in Africa. This has constrained growth and human capital development. This study examined the relationship between education human capital development and per capita income in Nigeria from 1986 to 2021. The data set for this study were sourced from the Central Bank of Nigeria (CBN) Statistical Bulletin of various issues and the Nigerian Bureau of Statistics (NBS). The Granger cuaslity test was employed. The analysis was anchored on the endogenous growth model. The result showed that education index and education expenditure were positively related to per capita income. The result further showed that capital expenditure, inflation and population growth, proxy for labour force were negatively related to per capita income, while health index and poverty headcount were positively related to per capita income. This paper recommended among other other policy options that the Government should promote and strengthened free and compulsory primary and secondary school enrolment so as to promote income of the citizenry.